Left double-lumen tube with or without a carinal hook. Issue 6 (June 2015) - Dumans-Nizard, Virginie; Parquin, Jean-François; Moyer, Jean-Denis; Dreyfus, Jean François; Fischler, Marc; Le Guen, Morgan
<x xml:space="preserve">Abstract</x> BACKGROUND Left double-lumen tracheal tubes (DLTs), with or without a hook to engage the carina, remain the standard device for lung isolation during anaesthesia. OBJECTIVE The purpose of the study was to compare these DLTs with and without a hook. DESIGN A randomised, controlled, single-blinded study. SETTING University hospital. PARTICIPANTS One hundred and eighty-four patients undergoing lung resection. MAIN OUTCOME MEASURE Time required to position the tube from the introduction of the tube into the mouth to confirmation of correct placement in the supine position. RESULTS Baseline characteristics were well balanced between the groups. Time to place DLTs was similar in both groups: median (interquartile range, IQR) 81.0 (50.0 to 146.2) s for DLTs without a hook and 67.5 s (45.0 to 138.7) for DLTs with a hook (P = 0.43). The incidence of adequate position at the first attempt was 68.5% in the No hook group and 69.6% in the Hook group (P = 0.95). Patients in both groups suffered similar incidences of sore throat at day 0 and day 1 (P = 0.80 and P = 0.20, respectively). No major lesion of the vocal cords or tracheobronchial tree was discovered and the incidence of minor lesions was similar in both groups. CONCLUSION When a DLT is used, the presence of a carinal hook gives neither advantage nor added complications. TRIAL REGISTRATION ClinicalTrials.gov, NCT00969683.